Structure and Dynamics of Research Collaboration in Computer Science - Bird, Christian; Barr, Earl; Nash, Andre; Devanbu, Premkumar; Filkov, Vladimir; Su, Zhendong (Proceedings of the Ninth SIAM International Conference on Data Mining, 2009)
Complex systems exhibit emergent patterns of behavior at different levels of organization. Powerful network analysis methods, developed in physics and social sciences, have been successfully used to tease out patterns that relate to community structure and network dynamics. In this paper, we mine the complex network of collaboration relationships in computer science, and adapt these network analysis methods to study collaboration and interdisciplinary research at the individual, within-area and network-wide levels. We start with a collaboration graph extracted from the DBLP bibliographic database and use extrinsic data to define research areas within computer science. Using topological measures on the collaboration graph, we find significant differences in the behavior of individuals among areas based on their collaboration patterns. We use community structure analysis, betweenness centralization, and longitudinal assortativity as metrics within each area to determine how centralized, integrated, and cohesive they are. Of special interest is how research areas change with time. We longitudinally examine the area overlap and migration patterns of authors, and empirically confirm some computer science folklore. We also examine the degree to which the research areas and their key conferences are interdisciplinary. We find that data mining and software engineering are very interdisciplinary while theory and cryptography are not. Specifically, it appears that SDM and ICSE attract authors who publish in many areas while FOCS and STOC do not. We also examine isolation both within and between areas. One interesting discovery is that cryptography is highly isolated within the larger computer science community, but densely interconnected within itself.